Design of a cooperative voltage harmonic compensation strategy for islanded microgrids combining virtual admittance and repetitive controller - Blanco, Cristian; Tardelli, Francesco; Reigosa, David; Zanchetta, Pericle; Briz, Fernando (2016)
Non-linear loads (NLLs) in three-phase systems are known to produce current harmonics at -5, 7, -11, 13... times the fundamental frequency; harmonics of the same frequencies are induced in microgrid voltage, reducing therefore the power quality. Dedicated equipment like active power filters can be used to compensate the microgrid harmonics; alternatively, each distributed generation (DG) unit present in the microgrid can be potentially used to compensate for those harmonics. The use of the virtual admittance concept combined with a PI-RES control structure has been recently proposed as a harmonic compensation sharing strategy when multiple DGs operate in parallel. The drawback of this methodology is that a large number of RES controllers might be required to compensate for all harmonic components induced by NLLs. This paper proposes the combined use of virtual admittance control loop and repetitive controller (RC) for harmonic compensation. The main advantage of the proposed method is that only one RC is required to compensate for all the harmonic components, significantly reducing the computational burden and the design complexity.